Poverty alleviation through micro-credit: Evidence of BRAC credit program (Journal of the Bangladesh Agricultural University, 2016)
The paper presents the extent of poverty alleviation through micro-credit of Bangladesh Rural Advancement Committee (BRAC) women beneficiaries in upgrading their economic and social status. The study was conducted three villages in Birampur upazila under Dinajpur district. Out of 442 populations, 88 women beneficiaries were randomly selected which constituted the sample. Data were collected during 20th February to 20th March,2009 using interview schedule. Coefficient of correlation(r) was computed in order to explore relationship between the selected characteristics of the women beneficiaries and their poverty alleviation. Only 4.5% population had high poverty alleviation while the highest proportion (61.4%) of the women had moderate poverty alleviation in participating BRAC micro-credit activities. The findings showed that age, family size and duration of involvement with BRAC had no relation with their poverty alleviation. Education, farm size, family income, Cosmo politeness, availability of BRAC micro-credit and attitude towards BRAC had positive relationship with their poverty alleviation. New loan is not issued until final repayment of installment as identified by the beneficiaries as the main problem.J. Bangladesh Agril. Univ. 13(1): 87-92, June 2015